Processamento de matéria orgânica em riachos tropicais: efeitos de planta exótica e da qualidade do detrito sobre a atividade dos decompositores. - Pazianoto, Laryssa Helena Ribeiro (2019)
Headwater streams are small environments dependent on the adjacent ecotone. They represent important water recharge sources for drainage basins, as well as, shelter, reproduction and feeding areas for organisms.The allochthonous material from riparian vegetation is the main source of energy, which becomes available through processing performed by aquatic organisms. Thus, modifications in the composition of the adjacent vegetation may alter the ecosystem functioning.Despite the importance of streams, invasion of riparian zones by exotic plant species has often been associated with impacts from anthropogenic activities, making them dispersion corridors.However, the extent of exotic plant species impacts depends not only on their presence, but also on their abundance and the leaf litter nutritional quality. Assessing impact-abundance relationships is important, because properties that confer high invasivenesswill not always reflect on ecosystem functioning. In turn, leaf litter nutritional qualityaffects the colonization and decomposers activity, as more palatable leaves (higher nutrients concentration) are preferentially colonized and decomposed at a higher rate. Invertebrates and microorganisms (bacteria and fungi) are the main responsible for the organic matterprocessing, but information about the colonization patterns and the negative effects of exotic plant species or leaf litter nutritional quality between groups are scarce. In order to answer these questions, decomposition experiments were performed throughlitter bagstechnique. This method represents an integrated approach, which considers biotic and abiotic effects.In the first experiment, we investigated the effects of the exotic plant species Psidium guajava L. on the decomposition rates, colonization and aquatic hyphomycetes and invertebrate’s activity and compared with the native Cariniana estrellensis (Raddi) Kuntze, considering a gradient between species abundances in litter bags. In the second approach, we evaluated the microbial compartment, investigating the colonization patterns between bacteria and aquatic hyphomycetes during the organic matter processing, as well as, the importance of leaf litter nutritional quality in the activity of these microorganisms.Studies that attempt to understand the functioning of tropical aquatic ecosystems are needed, especially those that evaluate invasion effects of riparian zones by exotic plant species, an increasingly frequent activity nowadays and in future scenarios.